Transfer of Inheritance to Adopted Children: A Comparative Study of Islamic Inheritance Law and Civil Law in Indonesia - Alfikrul Akbar; Ali Marzuki; Ratih Ayu Muflihah (PFL: Plural Family Law Review, 2026)
Despite the growing body of scholarship on Indonesian Islamic family law and civil inheritance, no study has systematically compared the two principal legal regimes governing adopted-child inheritance on the specific question of total estate transfer. This gap matters in practice: Indonesia’s pluralistic inheritance architecture comprising the Compilation of Islamic Law (KHI), the Civil Code (BW), and Staatsblad 1917 No. 129 applies different rules to different communities, generating recurring litigation and legal uncertainty for adoptive families. This article employs a normative-juridical comparative method, drawing on maqāṣid al-sharīʿah as the theoretical framework for evaluating the Islamic regime and on forced-heir doctrine for the civil-law regime, to examine whether the transfer of an entire estate to an adopted child can be juridically justified under each system. The findings show: first, that under Islamic inheritance law adopted children are not heirs (lacking nasab, musāharah, or walāʾ), but may receive at most one-third of the estate through wasiat wajibah (Art. 209 KHI) or hibah (Art. 210 KHI); second, that under the Civil Code equalization with legitimate children applies only to Chinese-descent Indonesians under Staatsblad 1917 No. 129, while all others depend on testamentary or inter vivos instruments subject to legitime portie; and third, that total estate transfer is excluded under both regimes, achievable only through heir consent or the absence of forced heirs. The comparative contribution lies in demonstrating that outcome convergence (reaching the same substantive result) coexists with doctrinal divergence (using different mechanisms), a finding with direct implications for Indonesia’s ongoing inheritance law reform debate.